Lipid ROS- and Iron-Dependent Ferroptotic Cell Death in Unicellular Algae Chlamydomonas reinhardtii - Ramachandran Srinivasan; Hyo-Shim Han; Parthiban Subramanian; Anbazhagan Mageswari; Seong-Hoon Kim; Srikanth Tirumani; Vaibhav Kumar Maurya; Gothandam Kodiveri Muthukaliannan; Mohandass Ramya (Cells, 2023)
The phenomenon of heat stress leading to ferroptosis-like cell death has recently been observed in bacteria as well as plant cells. Despite recent findings, the evidence of ferroptosis, an iron-dependent cell death remains unknown in microalgae. The present study aimed to investigate if heat shock could induce reactive oxygen species (ROS) and iron-dependent ferroptotic cell death in Chlamydomonas reinhardtii in comparison with RSL3-induced ferroptosis. After RSL3 and heat shock (50 °C) treatments with or without inhibitors, Chlamydomonas cells were evaluated for cell viability and the induction of ferroptotic biomarkers. Both the heat shock and RSL3 treatment were found to trigger ferroptotic cell death, with hallmarks of glutathione–ascorbic acid depletion, GPX5 downregulation, mitochondrial dysfunction, an increase in cytosolic calcium, ROS production, lipid peroxidation, and intracellular iron accumulation via heme oxygenase-1 activation (HO-1). Interestingly, the cells preincubated with ferroptosis inhibitors (ferrostatin-1 and ciclopirox) significantly reduced RSL3- and heat-induced cell death by preventing the accumulation of Fe2+ and lipid ROS. These findings reveal that ferroptotic cell death affects the iron homeostasis and lipid peroxidation metabolism of Chlamydomonas, indicating that cell death pathways are evolutionarily conserved among eukaryotes.